Primary School Management and Culture in Digital Transformation - Ly, Nguyen Thanh (VNU Journal of Science: Education Research; Vol 39 No 4DO - 10.25073/2588-1159/vnuer.4835, 2023)
This paper explores the opinions of managers, teachers and parents on Organizational Values and on management practices in enhancing these values in primary schools in Hanoi during digital transformation. The study involves 356 participants, including managers, teachers, and parents, in various educational primary institutions. By examining the real situation of these values and  management practices, this research aims to provide insights into effective leadership approaches that can facilitate successful digital transformation in schools. The findings highlight the importance of aligning management practices with the core values of the school culture to foster a supportive and innovative environment for all stakeholders involved. Implications for practitioners and recommendations for future research are discussed.